Epstein-Barr Virus Latent Membrane Protein 2A Contributes to Anoikis Resistance through ERK Activation - Iwakiri, Dai (American Society for Microbiology, 2013)
Epstein-Barr virus (EBV) is associated with various malignancies, including epithelial cancers. In this study, we analyzed the effect of EBV infection on epithelial cells by using EBV-converted epithelial cells. In EBV-positive cells, the extracellular signal-regulated kinase (ERK) pathway is constitutively activated. Inhibition of ERK activity leads to reduced anoikis resistance; therefore, EBV-positive cells are more resistant to anoikis, a type of apoptosis induced by cell detachment, than are EBV-negative cells. Among the viral genes expressed in EBV-positive cells, the latent membrane protein 2A (LMP2A) is responsible for induction of ERK-mediated anoikis resistance, although the expression level of LMP2A is much lower in EBV-positive cells than in EBV-transformed B cells. Further analysis demonstrated that LMP2A downregulation of the proanoikis mediator Bim through proteasomal degradation is dependent on the immunoreceptor tyrosine-based activation motif (ITAM). These findings suggest that LMP2A-mediated ERK activation is involved in the generation of EBV-associated epithelial malignancies.